Measuring customer satisfaction - Gerson, Richard F. (Crisp Pub. Menlo ParkUS, 1993)
Defines customer satisfaction. Provides reasons for measuring service quality and explains how to use 7 basic quality improvement measurment tools. Also provides methodology for measuring customer satisfaction and analysing data. Addresses need to manage customer satisfaction, and supplies samples of customer satisfaction surveys.